State-level variation in the cumulative prevalence of child welfare system contact, 2015–2019. (April 2023) - Yi, Youngmin; Edwards, Frank; Emanuel, Natalia; Lee, Hedwig; Leventhal, John M.; Waldfogel, Jane; Wildeman, Christopher
Highlights: Recent research using synthetic cohort life tables highlights the ubiquity of CPS contact at various levels (termination of parental rights, foster care placement, confirmed maltreatment, and investigation) at the national and, in some instances, county levels. This project contributes to that broader agenda by providing the first state-level estimates of each of these types of CPS contact by race/ethnicity and state of residence. Results highlight dramatic state-level variation in each of these levels of CPS contact. Abstract: Background: Prior estimates of the cumulative risks of child welfare system contact illustrate the prominence of this system in the lives of children in the United States (U.S.). However, these estimates report national data on a system administered at the state and local levels and are unable to detail potential simultaneous geographic and racial/ethnic variation in the prevalence of these events. Methods: Using 2015–2019 data from the National Child Abuse and Neglect Data System and Adoption and Foster Care Analysis and Reporting System, we use synthetic cohort life tables to estimate cumulative state- and race/ethnicity-specific risks by age 18 of experiencing: (1) a child protective services investigation, (2) confirmed maltreatment, (3) foster care placement, and (4) termination of parental rights for children in the U.S. Results: In the U.S., state-level investigation risks ranged from 14% to 63%, confirmed maltreatment risks from 3% to 27%, foster care placement risks from 2% to 18%, and risks of parental rights termination from 0% to 8%. Racial/ethnic disparities in these risks varied greatly across states, with larger disparities at higher levels of involvement. Whereas Black children had higher risks of all events than white children in nearly all states, Asian children had consistently lower risks. Finally, ratios comparing risks of child welfare events show these prevalences did not move in parallel, across states or racial/ethnic groups. Contribution: This study provides new estimates of spatial and racial/ethnic variation in children's lifetime risks of maltreatment investigation, confirmed maltreatment, foster care placement, and termination of parental rights in the U.S., as well as relative risks of these events.